Exploring Cafe Atmosphere and Service Excellence Effects on Customer Loyalty Globally - Rizki Amaliyah; Sumartik (Indonesian Journal of Law and Economics Review, 2024)
This study explores the impact of cafe atmosphere, menu diversity, and service excellence on customer loyalty at Istoria Cafe Sidoarjo. Using a quantitative approach with data from 97 respondents, the analysis reveals that cafe atmosphere significantly influences customer loyalty, while menu diversity shows no significant impact. Service excellence, however, plays a crucial role in enhancing customer loyalty. These findings highlight the importance of creating a captivating ambiance and providing exceptional service to foster customer loyalty in the competitive food and beverage industry, offering valuable insights for cafe owners and managers aiming to improve business performance. Highlight: Ambiance Affects Loyalty: Atmosphere influences customer loyalty at Istoria Cafe Sidoarjo. Service Key to Loyalty: Excellent service crucial for fostering customer loyalty. Menu Diversity's Role: Limited impact on customer loyalty identified in the study. Keyword: Cafe atmosphere, Menu diversity, Service excellence, Customer loyalty, Istoria Cafe Sidoarjo.